Non-linear return to human capital for workers of productive sectors in Indonesia - Fajar Wisga Permana; Nasri Bachtiar; Adrimas Adrimas (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
This study is aimed to investigate a typical return to human capital for workers of productive economic sectors in Indonesia. Instead of satisfying Mincer’s linearity assumption, we use a piecewise linear spline function in order to trace marginal returns to education and job tenure and to find out how large the returns to both variables could be moderated by certain variables. The research is conducted on 2609 individuals who work for Indonesian top-five productive sectors in 2016, as recorded in National Work Force Survey (SAKERNAS). We implement quantile regression analysis to produce three levels earning model. The result shows that the return to education varies across schooling level and apparently negative for academy schooling. We also find that job training participation does not always enhance the return to education especially for higher earning workers. The return to job tenure is found to diminish during career length. However, graduating from certain college majors significantly slowdown the diminishing return to job tenure and thus promoting better career. Based on these findings, we outline several ideas concerned to developing higher education and job training provision in national scale for more efficient supply of human capital in the productive sectors.